The Survival Effect of Chest Wall With or Without Regional Lymphatic Radiotherapy for Breast Cancer Patients With T3~4N0M0 - Li, Guanqiao; Yao, Jia; Chen, Junni; Cai, Baizhen; Lin, Xiangying; Chen, Zetan; Chen, Jiawei; Wang, Han; Yang, Shiping (Frontiers in Oncology, 2021)
Background: Peripheral lymphatic radiotherapy in patients with pT3N0M0 and pT4N0M0 breast cancer has been a matter of considerable debate among radiation oncologists. This is the first report in non-Caucasia population. Patients and Methods: The study included 165 pT3N0M0 and pT4N0M0 patients. Univariate, multivariate, propensity score matching (PSM) and Kaplan-Meier analyses were conducted to evaluate the survival of patients. We also review all the literature about regional lymph nodes radiation in T3-4N0M0 patients and summarize them with tables to compare with the present study. Results: The median follow-up duration was 58.7 months. Multivariate analyses showed that advance T stage and grade were dependent poor prognostic factors for OS, DMFS, LRFS and DFS between group A (chest wall radiation) and group B (chest wall and regional lymph nodes radiation). The overall survival (OS), disease -free survival (DFS), local relapse-free survival (LRFS) and distant metastasis-free survival (DMFS) rates were not significantly different between group A and group B. The 5-year OS rate was 92.3% vs 89.7 % for group A and group B, respectively (P=0.819). The 5-year LRFS rate was 94.9% vs 94.3 % for group A and group B, respectively (P=0.852). 54 pairs of patients were selected after propensity score matching (PSM) analysis was conducted. There was also no significant difference between group A and group B in regards to the OS, DFS, LRFS, and DMFS rates after PSM. The patients included in previous studies were all Caucasian, and our study was focused on non-Caucasian. The cases of previous studies were ten to twenty years ago, but our study has more recent cases. The radiotherapy techniques of previous studies were conventional, and the techniques used in our study were three-dimensional conformal radiotherapy (3DCRT) or intensity modulated radiotherapy (IMRT). . Conclusion: Both our study and previous studies suggested that regional lymph nodes radiation can not improve the survival rate for breast cancer patients with T3-4N0M0 in non-Caucasian population. Advance T stage and grade were the dependent poor prognostic factors for T3-4N0M0 patients.